Bank Financing to Small and Medium-Sized Enterprises (SMEs) in Colombia - Stephanou, Constantinos; Rodriguez, Camila (World Bank, Washington, DC, 2012)
The objective of this paper is to shed light on current trends and policy challenges in the financing of small- and medium-sized enterprises (SMEs) by banks in Colombia. The paper is motivated by the well-documented financing gap for SMEs, whose causes are complex and multi-dimensional. Based on data collection and interviews with the authorities, a representative sample of banks, and other relevant entities, the authors analyze the evolution and characteristics of this market in recent years. Bank financing to SMEs is becoming a strategic segment for Colombian credit institutions. The current business and risk management models for SME lending are still relatively underdeveloped, but greater sophistication is expected as the market matures. Important institutional and policy constraints to SME lending remain, but are not yet binding. In order to address these constraints before they "begin to bite", the authors identify and describe a potential policy reform agenda.